Energy, exergy and economic analysis of nano-enhanced phase change materials integrated solar photovoltaic thermal systems - Imtiaz, Ali (2023)
Solar photovoltaic (PV) is one of the most prominent solar technology that produces electrical energy. However, only 5-20% of solar energy is converted into electricity depending upon the PV technology; the remaining energy is wasted. The temperature of solar cells plays an important role in the PV systems' efficiency. The efficiency of PV systems decreases with an increase in solar cells' temperature. Photovoltaic thermal (PVT) systems are budding as an essential part of the solar application systems, which integrates photovoltaic (PV) and solar thermal collector in a single unit to produce thermal energy and electrical energy from intermittent solar radiation and solves the issue of overheating of PV systems at a certain extent. However, PVT systems cannot store thermal energy, and the electrical energy can be stored using well-established technology, i.e., electrochemical batteries. Phase change materials (PCMs) are latent heat storage materials which can be used for temperature regulation in PV systems and as thermal energy storage materials in PVT systems which can be used later in the absence of solar energy. Nevertheless, these PCMs suffer from low thermophysical properties and can be improved by incorporating different nanomaterials and known as nano-enhanced PCMs (NePCMs). The PVT system's performances are dependent on energy analysis. The energy reduction occurring in the systems can often be detected using exergy analysis. Thus, energy, exergy and economic analysis are needed to enhance the system efficiency from a performance and cost perspective. Therefore, this study's main objectives are: (a) to formulate PW/TiO2 and PW/TiO2-Gr binary composites; b) To characterize the thermophysical behaviour of NePCMs; c) to analyse the performance of the PVT system using the 3E approach; d) to simulate the performance of PCM and NePCMs integrated PVT system. The present study proposes the solution to the problem by formulating the TiO2 and TiO2:Gr binary composite (1wt% TiO2: 0.1, 0.5, 1 and 2 wt% of Graphene (Gr)) enhanced Paraffin wax (PW). Fourier transform infrared spectroscopy (FT-IR), Ultraviolet-visible spectrometer (UV-Vis), Thermogravimetric analyzer (TGA), Differential scanning calorimeter (DSC), Thermal property analyzer (TEMPOS) and Field emission scanning electron microscopy (FESEM) were used for material characterizations and thermophysical analysis. The latent heat and thermal conductivity of the PW/TiO2-Gr binary composites were found to be 10.02% and 179% higher than base PW respectively. The FT-IR spectra showed no chemical interaction between the PW and the nanoparticles. The TGA analysis confirmed improved thermal stability by the integration of the TiO2-Gr into PW. The light transmission of the prepared composite was reduced by 58.30% as compared to the base PW. In the present study, a serpentine flow absorber is proposed as a thermal collector for the PVT system that allows efficient extraction of heat energy. The designed PVT system was studied at three different mass flow rates (0.3, 0.5, and 0.7 litres per minute (LPM)). Techno-economic results showed levelized cost of energy, net present worth and payback time as 0.30 MYR/kWh, 127.22 MYR and 8.82 years respectively. Further, the NePCM-integrated PVT system simulation was also carried out at these three flow rates. At the optimal flow rate of 0.3LPM, it was determined that the overall energy efficiency of the PVT, PVT-PCM, and PVT-NePCM systems was 80.49%, 82.45%, and 83.65%, respectively. However, overall exergy efficiencies of 6.19%, 8.03%, and 8.45% were recorded for the PVT, PVT-PCM, and PVT-NePCM systems, respectively. The significance of current research contributes towards sustainable development goals (SDGs) number 7 and number 13, along with many applications for household purposes or in industries like preheated water.